Water resources in the twenty-first century: challenges and implications for action. - Rosegrant, Mark W. (International Food Policy Research Institute, 1997)
In this paper, Mark W. Rosegrant assesses global water supply and demand, describes in detail the forces contributing to water scarcity, and lays out a number of strategies for managing water in the future. Any solution, Rosegrant asserts, will need to involve both the careful exploitation of new sources of water and strong measures to stimulate more efficient use of water. Policies must treat water not as a free good, as they often do now, but rather as a scarce commodity that comes at a price. Cooperation between countries sharing the same water basin will also become increasingly important as water becomes more scarce.